1987
DOI: 10.1212/wnl.37.8.1400
|View full text |Cite
|
Sign up to set email alerts
|

Iodinated contrast agents in myasthenia gravis

Abstract: Administration of intravenous iodinated contrast agents has been reported to cause increased weakness in myasthenia gravis (MG) patients. We reviewed the records of 136 patients with MG who had at least one radiologic procedure involving intravenously administered contrast media. Seven patients (5.1%) had contrast reactions, which compares with the 5% rate of contrast reactions in the general population. Five patients had either a subjective or objective increase in weakness that could be explained by reasons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
1
11
2
1
Order By: Relevance
“…Although there are case reports and case series (9)(10)(11)(12)(13)(14) in the literature describing adverse outcomes (including myasthenic crisis) in patients with myasthenia gravis exposed to high-osmolality contrast material, the strength and validity of this relationship is even less clear for low-osmolality contrast material (15). None of the previous investigators compared their results with those in a control group of patients not exposed to contrast material, and most Table 2 Myasthenia Gravis-related Symptom Deterioration after Unenhanced and Contrast-enhanced CT Time to Deterioration and Symptoms Unenhanced CT (n = 155)* Contrast-enhanced CT (n = 112)* P Value † two of seven leading to unresponsiveness and/or death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are case reports and case series (9)(10)(11)(12)(13)(14) in the literature describing adverse outcomes (including myasthenic crisis) in patients with myasthenia gravis exposed to high-osmolality contrast material, the strength and validity of this relationship is even less clear for low-osmolality contrast material (15). None of the previous investigators compared their results with those in a control group of patients not exposed to contrast material, and most Table 2 Myasthenia Gravis-related Symptom Deterioration after Unenhanced and Contrast-enhanced CT Time to Deterioration and Symptoms Unenhanced CT (n = 155)* Contrast-enhanced CT (n = 112)* P Value † two of seven leading to unresponsiveness and/or death.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few case reports (9)(10)(11)(12)(13)(14) describing isolated examples of a myasthenic crisis that developed after exposure to intravenous high-osmolality iodinated contrast material. However, not only are these case reports anecdotal, they are also dated because Implication for Patient Care n Intravenous administration of low-osmolality contrast material should be considered among the list of medications known to exacerbate myasthenic symptoms, with an estimated risk of acute symptom deterioration of approximately 5%-6% above baseline (95% confidence interval: 0%, 12%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Conversely, 1 study has shown that occurrence of a myasthenic crisis because of intravenous injection of contrast is controversial. 13 Most patients in the reported cases became apneic immediately after intravenous injection of contrast material. In our patient, no signs were observed immediately or shortly after administering the contrast injection.…”
Section: Discussionmentioning
confidence: 87%
“…One systematic retrospective study on acute adverse events (within 24 h) associated with high-osmolality agents presented five patients with a subsequent exacerbation of their myasthenic weakness, although in each case, alternative explanations for the deterioration other than ICA administration were possible [14]. …”
Section: Introductionmentioning
confidence: 99%